The pathogenetic mechanism of choked optic disc in penetrating eye injuries causing sharply reduced intraocular pressure - V. I. Morozov (Российский офтальмологический журнал)
The paper presents the author's observations and the analysis of choked optic disc in patients with penetrating eye injuries and IOP drastically reduced to 6-9 mmHg. The normal tissue pressured of the disk is known to be 10 mmHg. These patients show a significant widening of the vessels of the eye cavity, an active transudation from the microcirculatory bed of the disc area, and the disc’s transudate tissue edema. One day after the surgery sealing the eye cavity, IOP exceeds the level of 10 mmHg, the transudation process terminates, and the congestion level in the disc drops. The author believes that this picture should only be considered as a syndrome of the choked optic disc only in cases of penetrating eye injuries with sharply reduced IOP // Russian Ophthalmological Journal, 2016; 2: 61-63 . doi: 10.21516/2072-0076-2016-9-2-61-63 .